2018
DOI: 10.7759/cureus.3086
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Policy Change in the Emergency Department: A Qualitative Approach to Understanding Local Policy Creation and the Barriers to Implementing Change

Abstract: IntroductionWith thousands of new medical trials released every year, health care policymakers must work diligently to incorporate new evidence into clinical practice.Although there are some broad conceptual frameworks for knowledge translation in the emergency department (ED), there are few user-centered studies that illustrate how local policymakers develop and disseminate new policies.ObjectivesOur study sought to evaluate the process by which new departmental policies are formed in ED, how new evidence was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…Furthermore, access to memory aids such as algorithms and simple protocols developed with staff and monitoring adherence of new screening practices through staff assessment helped to resolve these knowledge deficits. Similar to Shaikh et al (2018) [ 30 ], a lack of willingness to change practices within the ED was also a barrier with a lack of time to update knowledge and skills described as a consistent challenge.…”
Section: Discussion Of Findingsmentioning
confidence: 72%
See 2 more Smart Citations
“…Furthermore, access to memory aids such as algorithms and simple protocols developed with staff and monitoring adherence of new screening practices through staff assessment helped to resolve these knowledge deficits. Similar to Shaikh et al (2018) [ 30 ], a lack of willingness to change practices within the ED was also a barrier with a lack of time to update knowledge and skills described as a consistent challenge.…”
Section: Discussion Of Findingsmentioning
confidence: 72%
“…Resource limitations, a lack of culture change and cumbersome bureaucratic structures are well recognised as barriers to implementing change and understanding local policy creation in the ED (Shaikh et al, 2018 [ 30 ]). This synthesis further identified screening specific barriers to knowledge and skills development with staff finding screening protocols difficult to recall, particularly in a busy ED environment where constant updates complicated the process and were difficult to adhere too.…”
Section: Discussion Of Findingsmentioning
confidence: 99%
See 1 more Smart Citation
“…To our knowledge, there is no clear consensus on what the optimal process of policy creation is for an ED, due to unique environment at each institution. Shaikh et al 9 have identified five steps in policymaking process in the ED, starting with identification of the problem, creating a policy team, constructing the policy, implementing, and monitoring it and actively addressing barriers to ED policymaking throughout the process.…”
Section: Figurementioning
confidence: 99%